Treatment complication, pathologic response and survival rate after chemotherapy before surgery in locally advanced cervical cancer - Sareh Hosseini; Malihe Hasanzadeh Mofrad; Elahe Aghel; Fatemeh Homaei Shandiz; Zohre Yousofi; Soodabeh Shahid Sales; Marjaneh Farazestanian; Mona Joudi (Mashhad University of Medical Sciences, 2020)
Introduction: Cervical cancer is the second most common cancer in less developed countries. Chemoradiation is the standard treatment for advanced cervical cancer, but there is a lack of radiotherapy equipment in developing country. Therefore, this study was performed with aim to evaluate the pathologic response, treatment complication and survival rate of patients with locally advanced squamous cell carcinoma (SCC) of cervix who were not candidate for chemoradiation with use of chemotherapy before surgery. Methods: In this single group, before-after randomized clinical trial, 24 patients with FIGO stages IB2, IIA2, and IIB squamous cell carcinoma (SCC), who were not candidate for standard chemoradiation due to different causes, received 3 courses of neoadjuvant paclitaxel (135mg/m2)+ Cisplatin (75mg/m2) chemotherapy regimen. Then, surgery was performed. Clinical response to neoadjuvant chemotherapy and treatment side effects were assessed after each course. Wertheim hysterectomy was done 4 to 6 weeks later in those with favorable response. In the absence of major risk factors in the surgical pathology, patients received 3 additional cycles of adjuvant chemotherapy. In high risk patients, adjuvant chemoradiotherapy was performed. Data was analyzed by SPSS software (version 21) and Chi-square, and Kaplan Mayer tests. PResults: Among 24 patients, 13 cases (54.2%) and 17 (73.9%) had FIGO stageIIB and gradeII tumors, respectively. Parametrial involvement was presented in 13 patients (54.2%). Seven patients were excluded. 17 patients underwent surgical resection. Four high risk patients and were candidate for chemoradiation. Clinical and complete pathological response rate were 17 cases (70.8%) and 8 cases (47.1%), respectively. With a median follow up of 18.5 months, mean of overall survival and disease free survival of patients treated with the study protocol were 24.51 and 25.71 month, respectively. The mean of overall survival of whole patients (24 cases) was 30.8 month (CI: 95%, 29/38-32/26).  Conclusion: Neoadjuvant chemotherapy in patients with locally advanced cervical cancer despite acceptable pathologic response is not associated with survival advantage.